In Situ Microsensor Studies of Long-Term Environmental Effect of Sediment Dredging in the Shallow Lake - Qian, B.; Liu, L.; Yan, W.M.; Zhang, Y.; Xiao, X. (Asian Journal of Chemistry, 2012)
A laboratory experiment was carried out through a fifteen-month incubation of undredged and dredged cores to study the long-term effect of sediment dredging on biogeochemistry. The pH, redox potential (Eh), O2 profiles and the net rates of O2 production and consumption at different light intensities were measured at high spatial resolution by microsensors. The results showed that dredging the uppermost 30 cm sediment layer can effectively control the phosphorus release in long-term effectiveness. However, the dredged cores were vulnerable to disturbance and the microbial community which on the sediment surface before lake dredging would not be recovered in a long time in the future. Consequently, dredging may be not a satisfied measure for rehabilitating the aquatic ecosystem to control water eutrophication.